INVESTING BASED ON ESG FACTORS: METHODOLOGICAL APPROACH - Nasirov Egamkul (American Journals, 2024)
The article describes the role and significance of the “ESG” approach in ensuring the implementation of the objectives set by the UN sustainable development goals. The methodological foundations for regulating ESG activities at the international level and the methodology for assessing ESG factors of companies have been studied. Here, recommendations are given for the application of the ESG approach in the national economy.
Keywords: ESG factors, green economy, financial instruments, green investments, responsible investments, socially responsible investments, green financing, green projects.